Equidade intergeracional e direito das crianças ao meio ambiente: um caminho necessário. - Raquel Viegas Carvalho de Siqueira Biscola (2023)
This theme is developed in relation to the right to the environment from the perspective of the principles of human dignity, among which children are evidently included, and intergenerational solidarity, under which the right of future generations to the environment is examined. For this, it initially contextualizes the human right to the environment in the face of the current scenario of globalization and global ecological crisis. Next, it analyzes the environment from the perspective of solidarity, making brief distinctions of solidarity in relation to fraternity and on the claimability of the rights of solidarity. Broader considerations are made on the principle of intergenerational solidarity and, then, specific considerations, in addition to dealing with human dignity and children as subjects of the right to dignity. It brings a current overview of the international recognition of the right of children and future generations to the environment, with reference to the most emblematic judgments, and addresses a brief history of the main international instruments on the right to the environment, as well as the duties of the States related to the rights of children and future generations to the environment. It also reports the protagonism of children in acts that affect their well-being and the equation of environmental treaties with human rights treaties. Brings the brazilian constitutional provision, legal and specifically the Statute of Children and Adolescents. It suggests education as the main alternative to protect the right of children and future generations to the environment and lists other suggestions for its implementation. A preliminary bibliographic survey of international and national legislation was carried out. To examine the material obtained from the bibliographic research, the deductive and systematic methods were used. The type of research is exploratory in nature. The population concerns children and future generations in general and the respective right to the environment, as a community. International treaties and soft law instruments on the subject, articles, books and reports by national and international authors and organizations are analyzed.